2007
DOI: 10.1042/cs20060185
|View full text |Cite
|
Sign up to set email alerts
|

Chronic administration of genistein improves endothelial dysfunction in spontaneously hypertensive rats: involvement of eNOS, caveolin and calmodulin expression and NADPH oxidase activity

Abstract: The soya-derived phytoestrogen genistein has been suggested to be protective in cardiovascular diseases. In the present study, we have analysed whether chronic oral genistein might influence endothelial function in male SHRs (spontaneously hypertensive rats) via ERs (oestrogen receptors), changes in eNOS (endothelial NO synthase) activity and vascular O(2)(-) (superoxide) production. Rats (23-weeks old) were divided into the following groups: WKY (Wistar-Kyoto)-vehicle, SHR-vehicle, WKY-genistein (10 mg.kg(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 31 publications
5
53
0
1
Order By: Relevance
“…133,134 Genistein has been shown to improve endothelial function and upregulate antioxidant genes through ERK1/2 and NFB signaling pathways, both properties that may be beneficial for cardiovascular health. 135,136 In a recent study, genistein mimicked the actions of 17␤-estradiol in its ability to localize phospho-Akt to the nucleus in cultured cardiac myocytes, a potentially cardioprotective outcome. 75 It is unclear whether the mechanism of this cardioprotection by genistein is mediated through ERs or through some other mechanism.…”
Section: Phytoestrogensmentioning
confidence: 99%
“…133,134 Genistein has been shown to improve endothelial function and upregulate antioxidant genes through ERK1/2 and NFB signaling pathways, both properties that may be beneficial for cardiovascular health. 135,136 In a recent study, genistein mimicked the actions of 17␤-estradiol in its ability to localize phospho-Akt to the nucleus in cultured cardiac myocytes, a potentially cardioprotective outcome. 75 It is unclear whether the mechanism of this cardioprotection by genistein is mediated through ERs or through some other mechanism.…”
Section: Phytoestrogensmentioning
confidence: 99%
“…of three independent experiments, **P < 0.01 versus untreated control. studies shown that the beneficial effects of genistein were associated with the regulation on endothelial nitric oxide synthase (eNOS), because N-nitro-L-arginine methyl ester (L-NAME), the inhibitor of eNOS, abolished the restoration of endothelial function in healthy postmenopausal women (Mishra et al, 2000;Colacurci et al, 2005) and rats (Vera et al, 2007). Upon activation, eNOS produces and release endothelial nitric oxide, a crucial vasoactive molecule in maintaining vascular homeostasis because of its potent activity to relax vascular arteries, prevent intra-vasal coagulation and platelet aggregation and antagonize the proliferation of smooth muscle cells (Li and Forstermann, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Los mecanismos por los cuales los flavonoides de la soya mejoran la función endotelial también incluyen la producción de NO. Por ejemplo, genisteína aumenta la expresión así como la actividad de eNOS en ratas espontáneamente hipertensas (142)(143)(144).…”
Section: Marcadores De Inflamaciónunclassified